PENERAPAN TEKNIK MODELING MELALUI BIMBINGAN KELOMPOK UNTUK MENINGKATKAN MORALITAS SISWA MTsN 4 ACEH BESAR - Wanty Khaira; Evi Zuhara; Siti Sarah (FITRAH: International Islamic Education Journal, 2022)
Moral is a trait contained in the individual in actions that have positive and negative values carried out by humans. Moral improvement should be owned by every individual. However, what happened at MTsN 4 Aceh Besar was that there were several students who had bad morals in the school environment, such as labeling the teacher's name with another name, not respecting peers by body shaming against their friends and liking to mock friends' names using their parents' names. Therefore the research aims to determine the increase in student morality by applying modeling techniques through group guidance at MTSN 4 Aceh Besar. The research method uses a quantitative approach in the form of a one group pre-test-post-test design through two classes, namely the experimental class and the control class. The population in the study were 210 students in class VIII at MTsN 4 Aceh Besar and the sample in the experimental and control classes consisted of 8 students selected through a purposive sampling technique. Samples were taken based on the moral characteristics of students in class VIII-B and VIII-F, often displaying attitudes and behavior such as lack of respect for teachers, disrespect for friends, labeling the names of teachers and friends with other names, and never staying in class when PBM. Data collection techniques using student morality questionnaires. Data were analyzed using the t test with the help of SPSS. The results showed that there was an increase in student morality before and after being given group guidance services using modeling techniques. This is also proven by the results of the paired samples test (11,160> 1,761) it can be concluded that the hypothesis (Ha) is accepted while Ho is rejected.